Upaya Peningkatan Berat Badan Balita dengan Metode Pemberian Makan Tambahan Lokal dan Biskuit - Sholikah, Nurrochmatin; Sumaningsih, Rahayu; Sunarto, Sunarto; Nugroho, Heru Santoso Wahito (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2024)
The main problem is that the government's supplementary feeding program is still limited, so it has not been able to reach all under-fives with malnutrition and slow weight gain. So, it is necessary to provide alternative additional food. This study aims to accelerate the increase in body weight for toddlers with malnutrition by providing local additional food, namely from Moringa leaves because it is an ingredient that is easily available in the environment around the house, easy to process and easy to reach. The design of this research was pretest-posttest with control group. The research respondents were 18 toddlers with malnutrition who were recorded in the working area of the Takeran Health Center, who were selected by simple random sampling technique. The sample was divided into 2 groups, each of which was given local food additives and biscuits for 14 days. Data collection was carried out by measuring the toddler's weight before and after giving the treatment, then a difference analysis was carried out using a paired sample t-test. The results of the analysis for each showed the same p value in both groups, namely = 0.003, so it was interpreted that there was a significant difference in body weight between before and after being given additional food in the two groups. The results showed that local ingredients and biscuits had the same effectiveness in increasing the weight of malnourished toddlers.Keywords: toddler; malnutrition; supplementary feeding; moringa leaves; biscuitsABSTRAK Permasalahan utama yaitu program pemberian makanan tambahan dari pemerintah adalah masih terbatas, sehingga belum dapat menjangkau seluruh balita dengan kekurangan gizi dan peningkatan berat badan yang lambat. Maka, diperlukan pemberian makanan tambahan alternatif. Penelitian ini bertujuan mempercepat peningkatan berat badan balita dengan kekurangan gizi dengan pemberian makanan tambahan lokal yaitu dari bahan daun kelor karena merupakan bahan yang mudah didapat di lingkungan sekitar rumah, mudah diolah dan mudah dijangkau. Rancangan penelitian ini adalah pretest-postest with control group. Responden penelitian adalah 18 balita dengan kekuranan gizi yang tercatat di wilayah kerja Puskesmas Takeran, yang dipilih dengan teknik simple random sampling. Sampel dibagi dalam 2 group, masing-masing diberi pemberian makanan tamabahan lokal dan pemberian biskuit selama 14 hari. Pengumpulan data dilakukan dengan pengukuran berat badan balita sebelum dan sesudah pemberian perlakuan, selanjutnya dilakukan analisis perbedaan menggunakan paired sample t-test. Hasil analisis pada masing-masing menunjukkan nilai p yang sama pada kedua group yaitu = 0,003, sehingga diinterpretasikan bahwa ada perbedaan berat badan secara signifikan antara sebelum dan sesudah diberikan pemberian makanan tambahan pada kedua kelompok. Hasil penelitian menunjukkan bahwa bahan lokal dan biskuit memiliki efektifitas yang sama untuk meningkatkan berat badan balita gizi dengan kekurangan gizi.Kata kunci: balita; kekurangan gizi; pemberian makanan tambahan; daun kelor; biskuit